DETERMINAN PENGGUNAAN E-WALLET PADA KALANGAN MAHASISWA - Kusuma, I Komang Wahyu Buana; Latrini, Made Yenni (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.03.TAHUN.2025DO - 10.24843/EEB.2025.v14.i03.p07, 2025)
The rapid development of the digital era has reached various orders of life, without exception the payment system. Digitalization is one of the payment systems by switching conventional payment methods to digital payment methods with e-wallet services. This study aims to empirically examine the effect of perceived convenience, perceived benefits, and service quality on decisions to use e-wallets among students. The study population was undergraduate students of the 2020 batch of the Faculty of Economics and Business, Udayana University with a sample of 165 respondents determined by non-probability sampling using convenience sampling techniques. The hypothesis was tested with multiple linear regression. The results showed that perceived convenience had no effect on decisions to use e-wallets. Perceived benefits and service quality were found to have a positive effect on the decision to use e-wallets, thus indicating that the better the quality of the service resulted in the decision to apply e-wallets in financial transaction activities increasing. Theoretically, this research provides knowledge about the Technology Acceptance Model (TAM). Practically, the results of the study provide considerations for companies providing e-wallet applications to consistently provide the best convenience, benefits and quality of service for e-wallet users.